A novel and highly efficient Zr-containing catalyst supported by biomass-derived sodium carboxymethyl cellulose for hydrogenation of furfural - Hao, Jianxiu; Zhang, Yafang; Zhang, Tianyuan; Zhou, Huacong; Liu, Quansheng; Zhi, Keduan; Li, Na; He, Runxia (Frontiers in Chemistry, 2022)
Functional use of biomass based on its structural properties is an efficient approach for the valuable utilization of biomass resources. In this work, carboxymethyl cellulose zirconium-based catalyst (Zr-CMC) was constructed by the coordination between the carboxylic groups in sodium carboxymethyl cellulose (CMC-Na) with transition metal Zr4+. The prepared catalyst was applied into the synthesis of furfuryl alcohol (FAL) by catalytic transfer hydrogenation of biomass-derived furfural (FF) using isopropanol as hydrogen donor. Both the preparation conditions and the reaction conditions of Zr-CMC catalyst were investigated and optimized. The results showed that Zr-CMC was efficient for the reaction with the FF conversion, FAL yield and selectivity 92.5 %, 91.5 % and 99.0 %, respectively, under the mild conditions (90 °C). Meanwhile, the Zr-CMC catalyst could be reused at least for five times without obvious decrease in efficiency, indicating the catalyst had excellent stability. With the advantages of sustainable raw materials, high efficiency, and excellent stability, the prepared catalyst is potential for application in the field of biomass conversion.